Sport law and anti-doping education programs based on interdisciplinary approach - Dubrovin, O. V.; Titova, E. V.; Cherepov, E. A.; Erlikh, V. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes a variety of problems with concern to violations of the anti-doping laws in the interdisciplinary context. The valid provisions of the Russian anti-doping legislation are analyzed versus the relevant provisions of the World Anti-doping Code (WADC), with a special emphasis on the practical educational component of the anti-doping policies and practices in Russia. It is underlined that the anti-doping policies and practices in the national sports shall be based on a theoretically well-grounded progress of the anti-doping legislation and education. Model interdisciplinary anti-doping education programs designed to comply with the relevant (legal and sport) educational standards are offered for discussion. The educational model of our design offers an educational material formed by an interdisciplinary research laboratory based team including leading sport and legal experts, education specialists and sport federation analysts rather than a specific education division only.